Growth of the Waste of Electrical and Electronics Equipment Generation in India - Jaikumar, R. A.; Senthilkumar, R. A.; Radhika, S. (Asian Journal of Science and Applied Technology, 2015)
In this paper has deeply discussed and analysis with the Dumping of the Waste of Electrical and Electronics Equipments in public places , Growth of the WEEE and water resources are creating serious health hazards and unless and until it is controlled the reaction out of this world cause infection which would create a lot of disadvantage to the society . The major problem that the human race is facing now is the effects of the E-pollution caused by the waste of Electrical and Electronics Equipments. So, there should be a rule to prevent the people from damaging the ecosystem of our country to save nature to save people. The implementation of different ways for the prohibition of dumping WEEE should be sanctioned by the legal system. We should be activated by the Legal action to control the WEEE. An economic solution and different disiplinary are designed to achieve an optimal source to reuse and reduce the WEEE.